(untitled) (Research, Society and Development, 2022)
Of vital importance to the economy of Mato Grosso do Sul, soybean held the second position in the overview of the products exported in 2020, however, the state is distant from the main export terminals and with high dependence on the road modal. In view of this, the present study sought to evaluate the impact of the average cost of transportation on the price of Mato Grosso do Sul state soybean and the adoption of the practice of collaborative logistics as an alternative to reduce transportation costs. In order to calculate the average cost of road transport, the criteria established in the National Policy of Minimum Costs of Road Cargo Transport (PNPM – TRC) were followed as a guide. Analyzes were made for the vehicle compositions with 7 axles and 9 axles, originating in the municipalities of Maracaju, Ponta Porã and São Gabriel do Oeste and as destinations the port of Santos, Paranaguá and São Francisco do Sul. The results indicate that the vehicle compositions with 9 axles presented the lowest cost per ton transported for all routes analyzed and that, in the comparison between the current scenario and the ideal scenario that considers the adoption of the practice of collaborative logistics with the aggregate of routes Santos (route 1a), Paranaguá (route 1b) and São Francisco do Sul (route 1d) the reduction in the total financial cost for 7-axle compositions was R 49,936,261.64, representing a reduction of 5.24% and for 9-axle compositions the reduction in the total financial cost between the current scenario and the ideal scenario of the same aggregate route was R 43,462,818.45, representing also a reduction of 5.24%.